Comparison of the immune response between local manufactured and commercial inactivated Newcastle Disease Virus vaccine in a challenge trail with field isolated Newcastle Disease Virus - Ahmed, A. I.; M. Odisho, S.; N. Al-Gafari, R. (The Iraqi Journal of Veterinary Medicine, 2018)
Velogenic Newcastle Disease Virus was isolated from broiler chickens in Northern Iraq. An inactivated vaccine was manufactured locally using as seed virus ELD50/ml109 and then compared with commercial inactivated vaccine in an experimental study which included 120 broiler chicks divided into three groups (G1 unvaccinated control, G2 for commercial vaccine and G3 for local vaccine). The chicks were injected subcutaneously at 3 days old followed by booster Lasota live vaccine eye drop. Indirect ELISA technique was used to estimate the antibody titer from the collected sera of chicks at age 7, 17 and 27 days (pre-challenge) and challenged at 31 days old with the same virus. The results indicated that there were significant differences (P<0.05) between vaccinated group G2 and G3 at 27th day old and showed a high antibody level with high protection percentage compared with the control. G1 which shown no survival, 100% mortality and severe histopathological lesions, while in G2 and G3 was 43% and 87% respectively. Post-challenge antibody titers of survival chicks showed in G3 significantly over the G2 with less severe histopathological lesions. This study concluded that vaccine failure could occur due to factors of the immune status of the host, improper storage of vaccine, improper vaccination and variant pathogenic virus strain. More epidemiological surveillances are required to decide the actual impact of the disease in poultry farms and matching the vaccines.